1
$\begingroup$

Given that $a$ and $b$ are positive constants and $a>b$, solve the simultaneous equations.

$a+b=13$
$\log_6 a +\log_6 b= 2$

I have tried doing this but I can’t figure out what to do first. I am thinking that you take logs of equation $1$ but I’m not sure.

$\endgroup$
3
  • $\begingroup$ Hint: a sum of logs is... $\endgroup$ – Sean Roberson Sep 22 '18 at 8:18
  • $\begingroup$ $\log a+\log b=\log {ab}$ $\endgroup$ – For the love of maths Sep 22 '18 at 8:20
  • $\begingroup$ By learning a little MathJax/LaTeX (there are some links in the help center) you can format math to look much better, and avoid having to write comments about what is subscripts). $\endgroup$ – Henrik supports the community Sep 22 '18 at 8:26
1
$\begingroup$

$\log_6a+\log_6b=\log_6(ab)$

$\log_6x=2$ if and only if $x=6^2=36$

Can you go on now, without peeking at the spoiler?

\begin{cases}a+b=13\\ab=36\end{cases} has an obvious solution

$\endgroup$
1
$\begingroup$

It comes down to finding two numbers, given their sum $s$ and their product $p$ : $$\begin{cases}a+b=13\\ \log_6 a+\log_6 b=2\end{cases}\iff\begin{cases}a+b=13\\ \log_6ab=2\end{cases}\iff\begin{cases}a+b=13\\ ab=6^2=36\end{cases}$$ so $a$ and $b$, by the theory of quadratic equations, are the roots of $$x^2-sx+p=x^2-13x+36=0.$$ You can find the roots applying the rational roots theorem.

$\endgroup$
2
  • $\begingroup$ Thanks. How do you know that log a +log b = 36? $\endgroup$ – Eleanorm Sep 23 '18 at 7:41
  • $\begingroup$ Just because $\;\log_6(ab)=2\iff ab=6^2$. $\endgroup$ – Bernard Sep 23 '18 at 10:23
1
$\begingroup$

Taking the logarithm of a sum leads you nowhere. But taking the antilogarithm yields a product.

$$6^{\log_6a+\log_6b}=6^{\log_6a}6^{\log_6b}=ab=6^2=36.$$

You have reduced to a problem where the sum and product of two numbers is known. By the Vieta formulas, these are the solutions of the quadratic equation

$$x^2-13x+36=0.$$

$\endgroup$
-1
$\begingroup$

Hint: Writing $$\frac{\ln(a)}{\ln(6)}+\frac{\ln(b)}{\ln(6)}=2$$ with the first equation $$b=13-a$$ we get $$\ln(a)+\ln(13-a)=2\ln(6)$$ Using the law of logarithm we get $$\ln(a(13-a))=2\ln(6)$$ and $$a(13-a)=e^{2\ln(6)}$$ Can you finish?

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.